Layer-specific cholinergic control of human and mouse cortical synaptic plasticity - Matthijs B. Verhoog (Nature Portfolio, 2016)
Nicotinic acetylcholine receptors (nAChRs) are differentially expressed across cortical layers, yet it is unclear whether they show layer-specific effects on synaptic plasticity in the prefrontal cortex. Here, the authors compare nAChRs across L6 and L2/3 in human and mouse cortex and find they mediate opposite effects on synaptic plasticity.